PROSPEK PENERAPAN BIOTEKNOLOGI DALAM PEMANFAATAN DAN PENGEMBANGAN BIODIVERSITAS PADI LOKAL SULAWESI TENGGARA - Wijayanto, Teguh (Jurnal Agroteknos, 2013)
Biodiversity is high value genetic resources required for the good of human being. Globally, biodiversity has been degraded into a danger level.   Identification of problems, alternative solutions to protect, to conserve, and to utilize the biodiversity is a primary priority. The utilization of local rice cultivars, as a source of germplasm for rice breeding programs must get special attentions to protect the germplasm from vanishing. Biotechnology or genetic engineering technology provides an alternative way and a short cut in manipulating and producing improved plant varieties.  Different kinds of methods can be used to genetically engineer plant species. Since 1980s and ever since, many achievements and improvements have been made by scientists around the world in the area of genetic engineering, including genetic improvement of rice crops.   As an example, scientists have engineered transgenic rice crops that contain pro-vitamin A in the endosperm.  Pro-vitamin A is a substance that does not naturally occur in rice, but is urgently required to prefend human’s eye blindness. Another example, recently a group of scientist has developed super- rice strain that defies triple whammy of stresses (drought, salty-soils, and lack of fertilizer) simultaneously. Keywords: Biodiversity, biotechnology, genetic improvement, and local rice cultivars